Post Covid-19 Strategies and Pupils' Academic Performance in Rubuguri Town Council Kisoro District. - Twesigye, Posiano (Kabale University, 2024)
This descriptive study investigated the effectiveness of post-COVID-19 strategies implemented in primary schools within Rubuguri Town Council, Kisoro District. A descriptive research design was employed to provide a framework for interpreting the findings and understanding the current status of educational phenomena in the context of the pandemic. Simple random sampling was utilized to select schools, pupils, and teachers from the targeted population, ensuring representativeness and minimizing bias. Purposive sampling techniques were employed to select head teachers, recognizing their unique position as school administrators. Data collection methods included surveys, interviews, and document analysis, allowing for a comprehensive exploration of the research topic. The study found that a diverse range of post-COVID-19 strategies, including digital learning platforms, community engagement initiatives, and teacher professional development programs, had been implemented to address the challenges posed by the pandemic. The effectiveness of these strategies was evaluated through quantitative and qualitative analyses, revealing varying degrees of success and areas for improvement. The findings underscored the importance of ongoing assessment and refinement of post-COVID-19 strategies to optimize outcomes and ensure the continued education and well-being of students. Recommendations for future research and practice were provided, highlighting the need for longitudinal studies to assess long-term impacts and comparative analyses to identify effective practices across diverse contexts. Overall, this study contributed to the growing body of knowledge on post-pandemic education and informed evidence-based decision-making for educational stakeholders in Rubuguri Town Council, Kisoro District, and beyond.